Effect of Annealing Temperature on the Characterizations of Cobalt Ferrite Nanoparticles Synthesized via Co-precipitation (International Journal of Scientific Research in Science and Technology, 2024)
This study investigates the effect of annealing temperature on the structural and magnetic properties of cobalt ferrite (CoFe2O4) nanoparticles synthesized via the co-precipitation method. The results indicate that the annealing temperature significantly enhances the crystal size and quality, yielding well-defined, impurity-free CoFe2O4 crystals. Magnetic measurements reveal that both saturation magnetization (Ms) and coercivity (Hc) are improved with annealing. The nanoparticles exhibit a soft-magnetic, single-domain state up to an annealing temperature of 1200°C. They reach a critical size of 39.7 nm and begin transitioning to a multi-domain state. These findings highlight the crucial role of annealing temperature in optimizing the properties of CoFe2O4 nanoparticles for potential applications in magnetic recording media, magnetic resonance imaging, magnetic fluid hyperthermia, biosensors, drug delivery, and cell separation.